A scoping review of AAC research conducted in segregated school settings. (January 2022) - Iacono, Teresa; Douglas, Sarah N.; Garcia-Melgar, Ana; Goldbart, Juliet
Highlights: AAC research in schools has been predominantly in segregated settings. Many student participants in these studies lack functional use of AAC. There has been limited attention to academic or social skills, or friendships. Functional AAC may be thought needed before academic and social participation. Abstract: Background: School education for children with severe disabilities tends to occur in restricted or segregated settings, especially for students who require augmentative and alternative communication (AAC). Aim: We sought to understand the role played by AAC, especially in supporting students' academic learning and social participation in studies conducted in segregated school settings. Methods: We conducted a scoping review, searching five databases, supplemented by hand, ancestral and forward citation searches of studies published from 2000 to 2020 involving compulsory school-aged students and featuring AAC. Data were extracted and summarized regarding study and participant characteristics, and key findings. Result: Our search yielded 141 studies conducted in a segregated setting ( n = 129) or mixed settings ( n = 12). Most studies focused on communication skills ( n = 69); academic skills ( n = 27) and social participation ( n = 17) were addressed to a far lesser extent. Conclusions: Research into students requiring or using AAC has focused on teaching communication skills and far less on academic learning and social activities of classrooms and schools. There is a need for research that extends beyond functional communication into how AAC can promote access to these key aspects of school education.